Can human brands help consumers eat better? Influence of emotional brand attachment, self‐identification, and brand authenticity on consumer eating habits. Issue 3 (2nd December 2020) - Guèvremont, Amélie
Abstract: This research studies the positive role of culinary human brands in helping consumers improve their eating habits (i.e., eat healthier, adopt a varied diet, and cook more) through the influence of emotional brand attachment—induced by actual and ideal self‐congruence—and while considering the moderating role of perceived brand authenticity. An online questionnaire was administered to 501 adults from a panel. Participants had to meet specific criteria—having a strong interest in food and cooking and being highly attached to a culinary human brand. Results were analyzed through structural equation modeling. Results reveal the influence of attachment in helping consumers improve their eating habits. The role of connection with consumer identity in inducing attachment is supported and characterized by a greater impact of the actual self. The moderating influence of brand authenticity is confirmed. This research suggests that culinary human brands can positively influence consumer food‐related decisions by serving as relevant identity resources. Results indicate that focusing on authenticity is a promising strategy to pursue human brands. Overall, this research calls for brands to think about how they can positively impact consumer lives, more specifically by helping them make better food decisions, ultimately contributing to their well‐being.